Oral health-related quality of life in children: Part I. How well do children know themselves? A systematic review - TS Barbosa (Journal compilation 2008 Blackwell Munksgaard, 2008)
Paediatric oral disorders are likely to have a negative effect on the quality of life. Until recently, children’s oral health-related quality of life (OHRQoL) was measured using parents as informants. Instruments have now been developed, which have demonstrated that with appropriate questionnaire techniques, valid and reliable information can be obtained from children.